Optimization and Validation of RP-HPLC-UV/Vis Method for Determination Phenolic Compounds in Several Personal Care Products - Fasihuddin Badruddin, Ahmad; Mohammed, Akkbik; Zaini Bin, Assim (2012)
A sensitive and selective reversed phase HPLC method with ultraviolet-visible spectrophotometry detection has been optimized and validated for the simultaneous determination of phenolic compounds, such as butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT) as antioxidants, and octyl methylcinnamat (OMC) as UVB-filter in several personal care products. The optimum analytical conditions (280 nm as maximum wave length, 0.8 mL/min as flow rate, pH 3.5, mixture of phase A (acetonitrile) with phase B (water:acetic acid; 99:1; v/v) as mobile phase) were obtained by variation of flow rate, the pH value of phase B, different binary mixtures. The dynamic range was between 1 to 250 mg L-1 with relative standard deviation better than 0.25%, (n=4). Limit of detection for BHA, BHT and OMC were 0.196, 0.170 and 0.478 mg L-1, respectively. While limit of quantification for BHA, BHT and OMC were 0.593, 0.515 and 1.448 mg L-1, respectively. Recovery study was performed by spiking standard of phenolic compounds at four different concentration levels using external standard addition method. The recovery for BHA, BHT and OMC were ranged from 92.1-105.9%, 83.2-108.9% and 87.3-103.7%, respectively. The concentration ranges of BHA, BHT and OMC in 12 commercial personal care samples were 0.13-4.85, 0.16-2.30 and 0.12-65.5 mg g-1, respectively. The concentrations of phenolic compounds in these personal care samples were below than maximum allowable concentration in personal care formulation i.e up to 1% (w/w) for BHA, up to 0.5% (w/w) for BHT and up to 10% (w/w) for OMC